Study on Wastelands Including Saline, Alkali and Waterlogged Lands and Their Reclamation Measures - Planning Commission (Planning Commission, 1963)
The Committee on Natural Resources at their meeting held on 26th December 1961 approved a study on water-logged, saline and alkali lands and wastelands of India. The Technical Committee on Land, on 3rd January 1962, set up a Working Group with membership as below to carry out this study: Dr. B. N. Uppal, Agricultural Adviser, Punjab. Shri R. D. Dhir, Chief Engineer (Flood control), Central Water and Power Commission, New Delhi. Dr. R. V. Tamhane, Soil Conservation Adviser, Ministry of Food and Agriculture, Department of Agriculture.
Committee on Natural Resources Planning Commission